Posted by **david** on Wednesday, February 28, 2007 at 7:51pm.

not sure i did right

3(f+2)+9=13+5f

3f+6+9 = 13+5f

+9

3F+15 = 12+5F

GOT MIXED UP SOMWERE

HELP

3f +6 +9 = 13 + 5f

3f + 15 = 13 + 5f

2f = 2

f = 1

drwls is correct

You are doing OK up to this point:

3f + 6 + 9 = 13 + 5f

Now combine any like terms.

(We can combine 6 + 9 to equal 15.)

3f + 15 = 13 + 5f

Try to get the variable on one side of the equation. Let's subtract 5f from both sides. Whatever operation you do to one side of an equation you must do to the other side as well.

3f - 5f + 15 = 13 + 5f - 5f

-2f + 15 = 13

Now let's subtract 15 from both sides:

-2f + 15 - 15 = 13 - 15

-2f = -2

Divide both sides by -2 to get f by itself and solve the equation:

-2f/-2 = -2/-2

f = 1

Does this check with the original problem? Substitute 1 for f and check. It always helps to check your work!

I hope this will help.

Don't add 9. How did you get 12 anyway? get variables on one side and constants on the other.

THNX GUYS